Case study of Chinese and U.S. university, college of business partnerships: form, process, opportunities, and challenges - Borgia, Daniel; Bonvillian, Gary; Rubens, Arthur (North American Business Press, 2011)
This paper presents the experiences of three regional universities - one public and two private - that have established academic partnerships in business with Chinese institutions of higher education. The paper briefly highlights the process used by three universities to establish linkages with their Chinese partners, the relative success of these alliances, and the lessons learned in the process. Although many Western Universities have established partnerships with Chinese Universities, there remains an enormous unmet demand for Western business education in China. However, Western business schools must prepare themselves for the many challenges in establishing these partnerships.